Confinement Effect of Concrete-Filled Steel Tube Columns With Infill Concrete of Different Strength Grades - He, Liusheng; Lin, Siqi; Jiang, Huanjun (Frontiers in Materials, 2019)
Concrete-filled steel tube (CFST) columns are increasingly used in composite construction. Under axial compression, the steel tube will sustain partial axial force and meanwhile provides the confinement to the infill concrete. The high axial strength capacity of CFST columns is largely related to the confinement provided by the steel tube. Extensive studies on CFST columns have been conducted. Nevertheless, how to quantify the efficiency of confinement effect in CFST columns using concrete with different strength grades is still missing. To address this issue, a series of compressive loading tests on CFST columns were conducted in present study. The variable parameters studied include concrete strength and diameter-to-thickness ratio of the steel tube. Six CFST stub columns in total were designed and tested under uniaxial compression. Axial strength, stress state in the steel tube, confined concrete strength and confining pressure acting on the infill concrete were carefully investigated. Test results show that the confinement factor (defined as the ratio of the nominal strength of empty steel tube to that of the unconfined concrete) is the most dominant factor influencing the confinement effect, and a larger confinement factor gives higher confinement effect. The low-strength concrete exhibits better performance of ductility and confinement compared with the high-strength concrete. The index of equivalent confining pressure was used to quantify the level of passive confinement provided by the steel tube in CFST columns. Based on the test results, a method to quickly quantify the confining pressure provided by the steel tube was proposed.